MANAGEMENT ANALYSIS OF THE INDEPENDENCE DEVELOPMENT PROGRAM AT THE GUNUNG SINDUR CLASS IIA NARCOTICS CORRECTIONAL INSTITUTION - Putra, Michael Dwi; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the management of the independence coaching program at the Narcotics Correctional Institution Class IIA Gunung Sindur. The background of this research focuses on the process of fostering independence, which has just undergone nomenclature from a special prison that focuses on spiritual guidance to a narcotics prison that provides guidance that provides independence guidance for the provision of prisoners when they have finished serving their sentence following Correctional Law No. 22 of 2022. The research method used is qualitative and descriptive, which involves in-depth interviews and documentation studies to collect data from officers and prisoners. The results showed that the coaching program has been running according to the established guidelines, although there are still challenges in terms of the availability of resources, facilities, regulations, and the interest of prisoners. In terms of coaching facilities, this study recommends motivating prisoners and continuous training for officers and prisoners so as not to rely on third parties to maintain the quality and effectiveness of self-reliance coaching. Keywords : Fostering Independence; Inmates; Management; Prisons